2016
DOI: 10.1136/jclinpath-2016-203617
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase 2 is an adverse prognostic marker in androgen receptor-negative breast cancer

Abstract: HAS2 has been proposed to be a target for therapeutic intervention in cancer. Our findings suggested a possible antagonistic role of AR pathway on HAS2 function. It will be interesting to further investigate their precise interaction, which may have important implication in HAS2 targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…It represents the main hyaluronan synthetic enzyme in normal adult cells, and its activity is finely regulated [96]. HAS2 also regulates the developmental and reparation processes of tissue growth, and it may be involved in inflammation, cancer, pulmonary fibrosis and keloid scarring [55,86,97,98,99]. HAS3 is the most active isoenzyme and produces HA molecules with MW lower than 3 × 10 5 Da [60].…”
Section: Biology Of Hamentioning
confidence: 99%
“…It represents the main hyaluronan synthetic enzyme in normal adult cells, and its activity is finely regulated [96]. HAS2 also regulates the developmental and reparation processes of tissue growth, and it may be involved in inflammation, cancer, pulmonary fibrosis and keloid scarring [55,86,97,98,99]. HAS3 is the most active isoenzyme and produces HA molecules with MW lower than 3 × 10 5 Da [60].…”
Section: Biology Of Hamentioning
confidence: 99%
“…A study by Zhang et al [97] suggested that the tumor-promoting functions of HAS2 may be antagonized by the androgen receptor (AR) signaling pathway in AR+ IBC. AR signaling has tumor suppressive effect, particularly in ER+ cancers.…”
Section: Has2mentioning
confidence: 99%
“…The prognostic features concerned higher grade, lymphovascular invasion, basal-like breast cancer subtype, high Ki67 and basal marker expression. It is proposed that HAS2 expression in ARÀ breast cancer may serve as an independent adverse prognostic factor in patient survival [97].…”
Section: Has2mentioning
confidence: 99%
“…Similarly, the biochemical and synthetic properties of HAS isoforms are distinct: HAS1 is the least active isoenzyme and produces HMW hyaluronan from 2 × 10 5 to 2 × 10 6 Da. HAS2, which represents the main hyaluronan synthetic enzyme in normal adult cells, is more active than HAS1 and synthesises HA chains > 2 × 10 6 Da. It regulates the developmental and reparation processes of tissue growth, and may be involved in inflammation, cancer, pulmonary fibrosis and keloid scarring [7–11]. HAS3 is the most active isoenzyme and produces HA molecules with a MW lower than 3 × 10 5 Da. …”
Section: Ha As a Major Component Of The Ecmmentioning
confidence: 99%